IMPACT OF FINANCIAL REPORTING QUALITY ON INVESTMENT EFFICIENCY AROUND THE GLOBE - Khan, Muhammad Azhar; Safdar, Nabeel (PEOPLE: International Journal of Social Sciences, 2024)
In developed markets, the documented enhancement of investment efficiency due to financial reporting quality has yet to address the question of whether such a correlation persists in emerging, frontier, and diverse markets. This study investigates the association between financial reporting quality and investment efficiency across 21,741 publicly listed firms spanning 36 countries worldwide, encompassing developed, emerging, frontier, and other markets. Comprehensive accounting data spanning the years 2000 to 2022 is gathered for all listed firms in 40 industries across these 36 countries having 166,453 firms-year observations. Causal connections are examined through fixed-effect regression analysis, supplemented by additional tests and robustness checks utilizing alternative proxies. Concerns about endogeneity are mitigated through 2SLS analysis. The results reveal a positive impact of financial reporting quality on investment efficiency for firms in developed, emerging, frontier, and other markets. Our exploration of both over-investment and under-investment scenarios demonstrates a more pronounced link between financial reporting quality and investment efficiency in the underinvestment scenario. These findings contribute to the existing body of evidence, indicating that beyond its influence on investment efficiency in developed markets, the relationship between financial reporting quality and investment efficiency holds true globally. This encompasses emerging, frontier, and other markets, characterized by varying levels of reporting quality and financial frameworks